2005
DOI: 10.1111/j.1440-1827.2005.01866.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the BRAF gene in papillary thyroid carcinoma and in Hashimoto's thyroiditis

Abstract: The purpose of the present study was to investigate the frequency of BRAF mutations in human papillary thyroid carcinoma (PTC) and Hashimoto's thyroiditis (HT) and to evaluate the association of the BRAF mutation with the clinicopathological features of both of these thyroid disorders. A total of 51 PTC with no HT, 28 PTC with HT and 27 HT with no PTC were evaluated using DNA extracted from paraffin-embedded specimens. BRAF mutations were analyzed by direct DNA sequencing of the polymerase chain reaction (PCR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
53
3
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 20 publications
7
53
3
1
Order By: Relevance
“…In this study, we performed a multivariate analysis and revealed that CLT was an independent predictor for the low prevalence of (Monaco 2012), and we consistently found a strong association of CLT with female gender, regardless of BRAF mutation status. It has been suggested that concurrent CLT is significantly associated with a lower frequency of BRAF mutations (Kim et al 2005a, Kim et al 2009b), and we also observed that the BRAF mutation was significantly less frequent in conventional PTC patients with CLT (76.9% vs 86.6%, P!0.001). A recent study proposed that the prevalence of the BRAF mutation in patients with CLT has been underestimated by a dilution effect on the mutated alleles of infiltrating lymphocytes, which carry WT BRAF (Guerra et al 2012).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In this study, we performed a multivariate analysis and revealed that CLT was an independent predictor for the low prevalence of (Monaco 2012), and we consistently found a strong association of CLT with female gender, regardless of BRAF mutation status. It has been suggested that concurrent CLT is significantly associated with a lower frequency of BRAF mutations (Kim et al 2005a, Kim et al 2009b), and we also observed that the BRAF mutation was significantly less frequent in conventional PTC patients with CLT (76.9% vs 86.6%, P!0.001). A recent study proposed that the prevalence of the BRAF mutation in patients with CLT has been underestimated by a dilution effect on the mutated alleles of infiltrating lymphocytes, which carry WT BRAF (Guerra et al 2012).…”
Section: Discussionsupporting
confidence: 63%
“…On the other hand, some investigators have reported that PTC with the coexistence of CLT is less associated with ETE, advanced stage, LN metastasis and recurrence (Loh et al 1999, Kim et al 2009a, Lang et al 2014. Interestingly, in two previous studies focused on BRAF mutation status in patients with PTC with and without CLT in a Korean population, the BRAF mutation was found less frequently in subjects with CLT than without CLT (64% vs 90% and 72.9% vs 95.3% respectively) (Kim et al 2005a, Kim et al 2009b. Moreover, there was a study that suggested that concurrent CLT could antagonize PTC progression, even in BRAF-positive patients (Marotta et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, os dados são incompletos e conflitantes em algumas áreas, como, por exemplo, quanto às mutações BRAF. Um estudo para investigar essa hipótese (12) mostrou que cerca de 14% dos casos de tireoidite abrigavam as mutações BRAF, diferindo do estudo (15) que relatou resultados negativos.…”
Section: Discussionunclassified
“…15 In Korea, BRAF V600E mutation has been detected at a greater frequency in papillary thyroid carcinoma without concurrent Hashimoto thyroiditis than in papillary thyroid carcinoma with Hashimoto thyroiditis. 20,21 In this study, the mutation was found in 10 (56%) of 18 patients with background Hashimoto thyroiditis, but in 152 (79%) of 192 patients without Hashimoto thyroiditis (Table 3). To establish the correlation between Hashimoto thyroiditis, papillary thyroid carcinoma and BRAF V600E mutation, it is necessary to study as many cases of coexistent Hashimoto thyroiditis with papillary thyroid carcinoma as possible.…”
Section: Discussionmentioning
confidence: 99%